Diagnosis of ventriculo-arterial discordance (transposition of the great arteries) by contrast echocardiography. Issue 8 (August 1977) - Mortera, C; Hunter, S; Tynan, M
Abstract : The constant anatomical relation of the aortic arch and the pulmonary artery bifurcation permits echocardiographic differentiation of the two great arteries when viewed from the suprasternal notch. When this technique was employed with contrast echocardiography in 12 infants, 6 of whom had ventriculo-arterial discordance (transposition of the great arteries), it was possible to establish with certainty in all but 1 case which great artery was most directly connected to the systemic venous return.